Enlarging time-steps for solving one and two phase flows using the particle finite element method - Gimenez, Juan Marcelo (2016)
Fil: Gimenez, Juan Marcelo. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.